Survey: Digital Image Watermarking Technique (International Journal of Engineering and Computer Science, 2014)
The “Digital Image Watermarking” is the process of embedding information into a digital media without compromising the media’s value in a way that it is difficult to remove. This is basically used to hide the information from attackers.